PENERAPAN METODE SAW PADA SISTEM PENDUKUNG KEPUTUSAN PENERIMAAN BANTUAN SISWA KURANG MAMPU MENGGUNAKAN BAHASA PEMROGRAMAN PHP DAN DATABASE MYSQL (STUDI KASUS : SMAN 4 PAYAKUMBUH) - Mey Yuki Lestari; Yuhandri; Harkamsyah Andrianof (Jurnal Elektronika Listrik dan Teknologi Informasi Terapan, 2023)
In the world of education, computer technology is in great demand because it can facilitate various kinds of activities in schools such as the management of receiving aid for underprivileged students or what is known as scholarships. SMAN 4 Payakumbuh has a scholarship program, every year there is an increase in the number of applicants and there are certain quota limits which make it difficult for the selection team to receive assistance for underprivileged students, therefore there is the establishment of a new system to overcome the problems faced by the old system so that it can help the school select students who are eligible to receive assistance, reduce data redundancies, and can help the performance of SMAN 4 Payakumbuh to be efficient by using the SAW, PHP and MySQL methods, to be able to get assistance for underprivileged students it must be in accordance with predetermined criteria such as income parents, number of siblings, number of dependents, beneficiary and distance from home to school. The application of the system that has been designed can provide a good solution to the selection team at SMAN 4 Payakumbuh in determining students who are eligible to receive assistance quickly and precisely.